Development and validation of discriminatory dissolution procedure for poorly soluble glyburide - Singh, Sachin K; Srinivasan, K K; Gowthamarajan, K; Narayan, G B (Asian Journal of Pharmaceutics (AJP), 2014)
In the present study, parameters such as solubility, medium pH, surfactant type and dissolution behavior of formulations, influence of sink conditions, stability and discriminatory effect of dissolution testing were studied for the selection of a proper dissolution medium for glyburide (BCS Class II drug). Results of solubility data revealed that solubility increased with an increase in pH. Sink conditions were exhibited in the 0.05 M borate buffer pH 9.6, 0.05 M phosphate buffer pH 6.5 containing 0.1-2% (w/v) cetyl trimethyl ammonium bromide (CTAB) and 0.05 M phosphate buffer pH 7.4 containing 0.1- 2% CTAB (w/v), respectively. The 0.05 M phosphate buffer at pH 6.5 containing 0.1% CTAB (w/v) with an agitation speed of 50 rpm (USP II) showed a more discriminating drug release profile when compared with 0.05 M phosphate buffer at pH 7.4 containing 0.1% CTAB (w/v) with an agitation speed of 75 rpm. The spiked samples have shown better recovery at 50, 100 and 150% levels. There was no degradation, as observed in the mass spectrum of recovered dissolution samples when compared with the mass spectrum of standard drug solution, which promised that the method was specific and can be used for routine Quality Control analysis as well as for assessment of formulation variables in future dissolution studies of glyburide.